Voluntary Audit Committees and Financial Reporting: Korean Evidence*. (11th October 2020) - Doo, Seoyoung; Yoon, Sung‐Soo
Abstract: This study investigates whether and how a regulatory change in the appointment procedure of audit committees affects firms' choice of an auditor or a voluntary audit committee. It also investigates whether voluntary audit committees improve earnings quality. We find that relatively larger medium‐sized firms with high ownership concentration establish voluntary audit committees to reinforce the control of major shareholders and that these audit committees do not improve financial reporting. Our result that audit committees do not necessarily improve financial reporting calls for policymakers and capital market participants to devote greater attention to audit committee appointments.